Education Repeal Ordinance Act 1891 - Trinidad and Tobago (My University, 1891)
"An ordinance to repeal the Ordinance No.24 of 1875 intituled "An Ordinance to amend No.6 of 1870" intituled "An Ordinance with regard to Education."
Keywords: Educational legislation